Impact of Gig Economy and Emerging Challenges on Banking Sector – an Indian perspective - R., John Ranjith (Ushus Journal of Business Management, 2023)
This paper explores the magnitude of changes that is happening in the Indian banking sector in terms of the technology used, human resource deployed and change in the customer experience. The emergence of gig workforce has made banks rework their strategy. Here, we will describe how Indian banking sector is battling legacy systems and trying to adopt to latest technologies. The gig economy which has been playing a major role in many other sectors have not made a significant impact in the banking industry. The paper discusses the reasons this and gives a first-hand perspective of how the banking sector is getting disrupted.